Learning styles and academic achievement among building construction students - Mohamad, Mimi Mohaffyza (2013)
This study is conducted to identify how learning styles (LS) influence the students’ academic achievement based on cognitive mastery and vocational elements in Building Construction Subject (BCS) involving the students and teachers of Building Construction Course (BCC) from three secondary vocational schools in Johor. Descriptive case study was applied with quantitative and semi-structured interview as supporting components in this study. The quantitative data were gathered based on Felder and Silverman Learning Styles Model (FSLSM), FelderSoloman